1991
DOI: 10.1002/ejsp.2420210607
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison and the drive upward revisited: Affiliation as a response to marital stress

Abstract: To test

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
4
21
0
1
Order By: Relevance
“…Most of the participants attributed positive reactions from each directional comparison. When upward comparisons were made with other homicide survivors, the cold case homicide survivors reported potentially being helped by those in a "better place" and a desire to achieve their level of healing, supporting previous research that details this trend (Buunk et al, 1991;Montada et al, 1992;Morrell et al, 2011). The sample indicated that they felt a bond with others who had experienced a homicide.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Most of the participants attributed positive reactions from each directional comparison. When upward comparisons were made with other homicide survivors, the cold case homicide survivors reported potentially being helped by those in a "better place" and a desire to achieve their level of healing, supporting previous research that details this trend (Buunk et al, 1991;Montada et al, 1992;Morrell et al, 2011). The sample indicated that they felt a bond with others who had experienced a homicide.…”
Section: Discussionsupporting
confidence: 70%
“…Buunk, VanYperen, Taylor, and Collins (1991) conducted two studies to measure marital satisfaction and the use of upward affiliation (associating with individuals perceived as being in a better situation). Results indicated that women with high marital dissatisfaction preferred contact with women with higher levels of satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of recent survey studies have indeed shown that, when faced with distress and uncertainty, individuals are relatively more inclined to seek out social-comparison information (Buunk, 1995;Buunk, Schaufeli, & Ybema, 1994), and this also applies to uncertainty and distress in marriage (Buunk, VanYperen, Taylor, & Collins, 1991). This notion is directly relevant for women aiming at an egalitarian division of labor.…”
Section: Social Comparisonmentioning
confidence: 97%
“…Masculine communication is characterized by greater emotional restraint, whereas women can express their feelings and emotions more fully and freely VASYURA in a conversation. Buunk, Vanyperen, Taylor, and Collins (1991) point out that women express stronger tendency toward affiliation than men do. Tannen (1991) has shown that men and women follow different rules of communication behavior.…”
Section: Palabras Clave: Actividad Comunicativa Género Individualidmentioning
confidence: 95%